Caregiver Report of the Utilization of School-Based Services and Supports Among Clinically Anxious Youth. (June 2021) - LoCurto, Jamie; Pella, Jeffrey E.; Chan, Grace; Ginsburg, Golda S.
Despite the high prevalence of and documented impairment associated with pediatric anxiety disorders, less than half of youth access mental health services. This study examined (a) the utilization of eight school services and supports (e.g., seen a school counselor for a mental health reason, placement in a special class for a behavior or emotional difficulty) and (b) demographic (gender, age) child clinical (anxiety severity and impairment) and family (parent psychopathology, caregiver strain) predictors of service utilization. Participants included 208 anxious youth between ages 6 to 18 years ( M = 10.92, SD = 3.29, 51% male, 64% White) who were enrolled in a school-based randomized controlled trial for anxiety treatment; only baseline data were used for this study. Parents, children, teachers and independent evaluators completed measures of the above predictors. Results indicated that less than half (48%) of youth received school services for anxiety. Several predictors of higher total service utilization were identified. Youth with comorbid externalizing behaviors were more likely to be referred for and receive school-based services. Consistent with published data in community samples, less than half of anxious youth received needed services. Results suggest a need for improvements in school assessments and service referral mechanisms for students with anxiety.